ANALISIS INVESTASI PENDIRIAN KONDOTEL X DI SANUR-BALI - Dwita, Made Ngurah Ananda; Wiksuana, I Gusti Bagus; Artini, Luh Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
Condotel X is located on Jalan Danau Tamblingan, Sanur - Bali is built on a land area of 1,970m2. This research examines the investment of the investor buyer Condotel. The study results showed the market and marketing aspects of the development are eligible, because there are still have opportunities in 2017 amounted to 5,880 rooms, while in 2018 as many as 4,338 rooms. based on the marketing aspect is feasible, because the company already knows the position of the company and can further implement the strategies that have been prepared before. The study results also showed that the financial aspects of the development are eligible, this is shown by NPV (Positive) amounting to Rp 11,321,369,440. The project's ability to return capital kondotel measured by IRR of 16.89%> 13.8% (cost of capital weighted average), Profitability Index 1.20> 1 and a payback period within 6 years and 2 months.
Keywords: Market Feasibility Aspects, Marketing and Financial Aspects